Evaluation of One-Dimensional Multi-Directional Site Response Analyses Using Geotechnical Downhole Array Data in California and Japan. Issue 1 (February 2018) - Li, Gangjin; Motamed, Ramin; Dickenson, Stephen
This study presents a comprehensive investigation of one-dimensional (1-D) site response analysis (SRA) to predict the dynamic response of soil deposits under earthquake loading utilizing the recordings at selected borehole arrays. Seven instrumented downhole arrays in California and Japan were studied using 41 recorded ground motions that cover a broad range of intensities. The arrays were initially assessed in terms of effectiveness of 1-D SRA using taxonomy screening. Furthermore, LS-DYNA, an advanced Finite Element (FE) program, was employed to develop the 1-D soil column models for the SRA of these arrays. The soil stress-strain behavior was characterized with three different models including one linear elastic and two nonlinear backbone curve formulations. All predictions were compared to the measured ground motions to quantify the model biases and uncertainties. Lastly, the practical limitations of 1-D SRA models considered herein are identified, and recommendations are provided to assess the usefulness of the predictions in engineering practice.